The impact of digital technology adoption and internationalization on manufacturing firms’ performance in China - Huang, Jianhong; Raja Yusof, Raja Nerina; Abd Rahman, Azmawani; Ab Rahman, Rozanah (Universiti Putra Malaysia, 2025)
Emerging digital technologies are driving the digital transformation of manufacturing, reshaping global supply chains, and introducing new challenges. Existing research highlights the role of individual technologies, such as additive manufacturing, the Internet of Things, and big data analytics in increasing efficiency and flexibility in global operations. However, only a few studies have examined the collective impact of these technologies on firms’ internationalization processes and performance, especially in emerging economies. This study addresses this gap by applying the Uppsala model to explore the links between digital technology adoption, internationalization, and performance. Survey data from 336 Chinese manufacturing firms, analyzed using structural equation modeling, indicate that both technology adoption and internationalization positively affect performance, with internationalization partially mediating this relationship. These findings underscore the importance of aligning digital technology adoption with internationalization strategies to enhance competitiveness, providing valuable insights for managers and policymakers on leveraging digital transformation for global success.